KINERJA KEUNGAN LEMBAGA PERKREDITAN RAKYAT SEBELUM PANDEMI COVID 19 - Ni Luh Putu Widhiastuti (Universitas Boyolali, 2022)
Financial performance is important because it shows the ability of the LPD to generate profits in a period that can be used as a basis for future decision making and evaluating what has been achieved. This research was conducted with the aim of knowing the effect of non-performing loans, savings growth, deposit growth, credit growth, asset growth and operating income operating expenses on financial performance. The population in this study was conducted at the Village Credit Institution in Badung Regency from 2018 to 2019. The sample determination method used was purposive sampling, so that a total sample of 214 LPDs was obtained. The analysis technique used is multiple linear regression analysis. The results of this study indicate that non-performing loans, savings growth, deposit growth, and asset growth have no effect on financial performance, while credit growth has a positive effect on financial performance and operating expenses for operating income have a negative effect on financial performance. Further researchers can conduct research again on LPDs in Bali and add other variables such as the capital adequacy ratio.